(untitled) (International Journal of Engineering and Computer Science, 2015)
We are living in an information age and there is enormous amount of data that is flowing between systems, internet, telephones, and other media. The data is being collected and stored at unprecedented rates. There is a great challenge not only to store and manage the large volume of data, but also to analyze and extract meaningful information from it. There are several approaches to collecting, storing, processing, and analyzing big data. The main focus of the paper is to draw an analogy for data management between the traditional relational database systems and the Big Data.